Smartphone App for Heart Rate Monitoring and Its Impact on Education Toward Industry 4.0 - Aripriharta, Aripriharta; Andajani, Kusubakti; Aisyah, Siti; Riski, Akhmad Afrizal; Andoko, Andoko; Mufti, Nandang; Horng, Gwo Jiun (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2020)
This paper presents the development of Smartphone app for monitoring the heart rate, which used as a tool for life-based learning. The app featured life-based experiments for undergraduates' students through do-it-by-your-self activities. This app was developed with Firebase to create a heart rate monitoring system interface as well as a framework for life-based experiments. Also, this app had video features as learning resources. We used an experimental method to evaluate the proposed system of learning. The subjects were 30 undergraduate students who were separated into two groups. Based on our survey, student learning outcomes increased by 35 percent compared to conventional experiments.